CURRENT ISSUES REGARDING THE PROSPECTS OF CONDUCTING SOME SPECIAL ACTIVITIES WITH PRISONERS OF WAR OF THE RUSSIAN FEDERATION - Mynko, Oleksandr (Honor and Law, 2023)
The conditions of detention of prisoners of war who are the citizens of the Russian Federation and are held in the institutions of the State Penitentiary Service of Ukraine have been analyzed. The typical character of the behavior of servicemen of the Armed Forces of the Russian Federation from the moment they were captured was considered. Examples of the use of servicemen of the Russian Federation after returning from custody (exchange) in the interests of enemy's propaganda and re-engagement in hostilities on the territory of Ukraine are given. The prospects for the emergence of protest movements within the Russian Federation are considered in view of the examples of the past and the realities of the present. A number of special activities, which are expedient to carry out with prisoners of war of the Russian Federation during their custody in places of detention on the territory of Ukraine, are proposed for consideration. Historical, legal, information-propaganda, religious, social, political, and intelligence-recruitment activities are appropriate to be considered such measures. Prospective results of the proposed special activities with prisoners of war and their possible consequences after return from custody (exchange) are considered.